Bacterial Keratitis: A Retrospective Review of 10 Years of Cultures - Serras-Pereira, Rita (2022)
INTRODUCTION: The purpose of this study is to evaluate demographic features, risk factors, bacterial isolates, antibiotic resistance patterns and therapeutic approach of bacterial keratitis over a period of 10 years in a tertiary referral hospital in Lisbon. M E T HO D S : Retrospective review of all bacterial keratitis diagnosed between 2009 and 2019. RESULTS: A total of 350 patients were diagnosed with bacterial keratitis between 2009 and 2019. Mean age was 54.77 years and 55% of patients were female. Based on first clinical observation, 72.3% of patients were classified as having serious keratitis and 60.86% were managed as in-patients. Contact lenses were the major risk factor identified (30.3%), followed by previous keratoplasty (11.1%) and ocular trauma (10.9%). Cultures were positive for bacteria in 56.86% of patients, with gram-negative bacteria comprising more than half of the isolates (52.26%). Pseudomonas aeruginosa was the most common single isolate (16.3%). Monotherapy with fluoroquinolones was given to 5.7% of patients and 75.4% were treated with fortified drops of ceftazidime and vancomycin. As for outcomes, 41 patients (11.7%) were submitted to a corneal transplant and five patients were eviscerated. CONCLUSION: Bacterial keratitis is a potentially blinding condition that leads to a great number of emergency department visits and inpatient care. Over the last 10 years, Pseudomonas aeruginosa has been the single most common bacterial isolate and contact lens wear the most frequent risk factor for bacterial keratitis in our center. Identifying bacterial isolates and their resistance pattern is of utmost importance for optimal management of patients.